An Analysis of the Health of SOE Bank (Conventional) With the Methodcamels Listed on BEI - Dessy Adriana Pakpahan; Rahima Boru Purba; Oktarini Khamilah Siregar (SIASAT, 2022)
This study aims to test and analyze the soundness of state-owned banks using the Capital, Assets, Management, Earning and Liquidity methods and sensitivity to market risk listed on the Indonesia Stock Exchange for the 2018-2020 period. This type of research is descriptive qualitative. The population of this study is state-owned banks listed on the Indonesia Stock Exchange from 2018 to 2020. The sampling method is census. The results showed that the soundness of Bank Negara Indonesia (Persero), Tbk, the soundness of Bank Rakyat Indonesia (Persero), Tbk, Bank Mandiri (Persero), Tbk, State Savings Bank (Persero), Tbk calculated by the CAMELS method as a whole showed that Healthy predicate.